Pengaruh Faktor Ekonomi Dan Indeks Saham Luar Negeri Terhadap Indeks Harga Saham Gabungan - Baroleh, Zefanya F. Baroleh F (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
Investors often make investment decisions based on the psychological aspects that make the investment decisions irrational. This decision was taken by looking at the sentiments that occurred because of the company's external factors. These external factors are economic factors in the country and the index of movement of stocks abroad. This study discusses economic factors and indexes of foreign stocks on the Indeks Harga Saham Gabungan. The results of this study found the variable rate of USD / IDR, the Dow Jones and Shanghai Composite Index partially had a significant effect on the temporary Indeks Harga Saham Gabungan, interest rates, net foreign funds, JPY / IDR, CNY IDR and NIKKEI225 partially did not significantly influence the Indeks Harga Saham Gabungan. Meanwhile, all variables simultaneously related significantly to the Indeks Harga Saham GabunganKeywords: Economic Factors, Overseas Stock Index, IHSG